Latter-day screens : gender, sexuality, and mediated Mormonism - Weber, Brenda R., 1964- (Duke University Press, 2019)
Brenda R. Weber examines the ways in which the mediation of Mormonism through film, TV, blogs, YouTube videos, and memoirs functions as a means through which to understand conversations surrounding gender, sexuality, spirituality, capitalism, justice, and individualism in the United States.